LUDUS LOVE IN POPULAR YOUTH PANTUNS ON TIKTOK: A HERMENEUTIC STUDY - Cahya Nabila; Wachid Eko Purwanto (Curricula: Journal of Teaching and Learning, 2025)
This study explores the expression of ludus love in popular teenage pantuns on the social media platform TikTok. According to the Oxford English Dictionary, ludus refers to a playful and non-committal type of love. John Lee (1973) classified ludus as a love style that prioritizes amusement and light-hearted interaction rather than deep emotional commitment. Such characteristics align with the nature of today's digital youth communication, which is expressive, instantaneous, and algorithm-driven. This research applies Paul Ricoeur's hermeneutic approach, which consists of three interpretive stages: explanation (structural analysis), understanding (contextual interpretation), and appropriation (reader's internalization of meaning). This method provides a comprehensive framework to uncover symbolic meanings embedded within seemingly simple pantuns. The analysis of pantuns reveals three dominant forms of ludus love: playful love, flirtatious love, and love without commitment. These forms serve not only as emotional expressions but also as strategic tools for communication and identity construction in digital youth culture. Consequently, digital pantuns are no longer seen merely as traditional verse but have transformed into performative and symbolic media reflecting the dynamics of contemporary teenage romance..